Random regression models for milk, fat and protein in Colombian Buffaloes - Hurtado-Lugo, Naudin [UNESP]; Tonhati, Humberto [UNESP]; Aspilcuelta-Borquis, Raul [UNESP]; Enriquez-Valencia, Cruz [UNESP]; Ceron-Munoz, Mario (Univ Cordoba, 2015)
Objective. Covariance functions for additive genetic and permanent environmental effects and, subsequently, genetic parameters for test-day milk (MY), fat (FY) protein (PY) yields and mozzarella cheese (MP) in buffaloes from Colombia were estimate by using Random regression models (RRM) with Legendre polynomials (LP). Materials and Methods. Test-day records of MY, FY, PY and MP from 1884 first lactations of buffalo cows from 228 sires were analyzed. The animals belonged to 14 herds in Colombia between 1995 and 2011. Ten monthly classes of days in milk were considered for test-day yields. The contemporary groups were defined as herd-year-month of milk test-day. Random additive genetic, permanent environmental and residual effects were included in the model. Fixed effects included the contemporary group, linear and quadratic effects of age at calving, and the average lactation curve of the population, which was modeled by third-order LP. Random additive genetic and permanent environmental effects were estimated by RRM using third-to-sixth-order LP. Residual variances were modeled using homogeneous and heterogeneous structures. Results. The heritabilities for MY, FY, PY and MP ranged from 0.38 to 0.05, 0.67 to 0.11, 0.50 to 0.07 and 0.50 to 0.11, respectively. Conclusions. In general, the RRM are adequate to describe the genetic variation in test-day of MY, FY, PY and MP in Colombian buffaloes.

Objetivo. Fueron estimadas funciones de covariancia para los efectos genéticos aditivos y de ambiente permanente, y posteriormente fueron estimados los parámetros genéticos para la producción de leche en el día del control (PDC) para leche (MY), grasa (FY), proteína (PY) y producción de queso mozzarella (MP), usando modelos de regresión aleatoria (RRM) mediante Polinomios Ortogonales de Legendre (LP) en búfalos de Colombia. Materiales y Métodos. Fueron analizados 1884 registros de PDC de primeras lactancias para MY, FY, PY y MP, hijas de 228 reproductores. Los registros procedían de 14 rebaños entre 1995 y 2011. Para las PDC fueron consideradas 10 clases mensuales de días en lactancia. Los grupos contemporáneos fueron definidos como rebaño-año-mes de control. Fueron incluidos en el modelo efectos aleatorios genético aditivo, de ambiente permanente y residual. Los efectos fijos incluidos fueron grupo contemporáneo, efecto lineal y cuadrático de edad al parto, y curva promedia de la lactancia de la población, la cual fue modelada por un LP de tercera orden. Los efectos aleatorios genético aditivo y de ambiente permanente fueron estimados por RRM mediante LP de tercero a sexto orden. Las variancias residuales fueron modeladas usando estructuras homogéneas y heterogéneas. Resultados. Las heredabilidades para MY, FY, PY y MP variaron de 0.38 a 0.05, 0.67 a 0.11, 0.50 a 0.07 y 0.50 a 0.11, respectivamente. Conclusiones. En general, los RRM son adecuados para describir la variación genética para la PDC de MY, FY, PF y MP en búfalos de Colombia.
Modelos de regresión aleatoria para leche, grasa y proteína en búfalos de Colombia
Keywords: Cattle; genetics; Zootechnics (Source: EuroVoc); Bovino; Genética; Zootecnia (Fuente: EuroVoc)